Dust and dignity : domestic employment in contemporary Ecuador - Casanova, Erynn Masi de, 1977- (ILR Press, an imprint of Cornell University Press, 2019)
"Through the understudied case of Ecuador, this book separates the exploitation inherent in domestic work from the exploitation that specifically affects migrant women workers"--